ANALYSIS OF STUDENTSâ DECISION MAKING TO SOLVE SCIENCE REASONING TEST OF TRENDS IN INTERNATIONAL MATHEMATICS AND SCIENCE STUDY (TIMSS) - Novianawati, N.; -, Nahadi (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This study aims to determine studentsâ decision making strategy to answer TIMSS science reasoning test in cognitive reasoning domain. This research is quantitative descriptive research. The result shows that students tend to use compensatory strategy for decision making in solving multiple-choice questions and use rational category to answer essay questions. The result shows that more than half of students have been able to answer the questions TIMSS science tests correctly.